2018
DOI: 10.1017/s0144686x18001605
|View full text |Cite
|
Sign up to set email alerts
|

‘I've got lots of gaps, but I want to hang on to the ones that I have’: the ageing body, oral health and stories of the mouth

Abstract: The mouth may be presented and understood in different ways, be subject to judgement by others and, as we age, may intrude on everyday life due to problems that affect oral health. However, research that considers older people's experiences concerning their mouths and teeth is limited. This paper reports on qualitative research with 43 people in England and Scotland, aged 65–91, exploring the significance of the mouth over the lifecourse. It uses the concept of ‘mouth talk’ to explore narratives of maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Individual oral health experiences are thus shaped by the actions of other people in the past, or the potential impact of actions on others in the future. Our work demonstrates that the mouth is relationally constituted through ‘mouth talk' (Warren et al . Forthcoming) embedded and practiced within family relationships.…”
Section: Families and Relational Narratives In Oral Health And Dentistrymentioning
confidence: 61%
See 3 more Smart Citations
“…Individual oral health experiences are thus shaped by the actions of other people in the past, or the potential impact of actions on others in the future. Our work demonstrates that the mouth is relationally constituted through ‘mouth talk' (Warren et al . Forthcoming) embedded and practiced within family relationships.…”
Section: Families and Relational Narratives In Oral Health And Dentistrymentioning
confidence: 61%
“…Considering how participants constructed their own mouths and teeth as relational through ‘mouth talk' (Warren et al , Forthcoming), we have shown how individual embodied experiences could be reframed. We have shown how narratives of oral health point to the contextuality, contingency and relationality of how oral health is experienced over the life course, as in the case of residential histories (Mason ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…From a phenomenological perspective, this process involves bodily “dys‐appearances”: that is, reminders or awareness of one's body—in this case, one's mouth and teeth—due to health problems or pain, when more routinely the body is forgotten about, an absent presence . Failure is judged on the basis of whether or not the work both fits and works in everyday life.…”
Section: Resultsmentioning
confidence: 99%